2014
DOI: 10.4049/jimmunol.1400399
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Negatively Regulates the Production of Inflammatory Cytokines/Chemokines and IL-17 in Visceral Leishmaniasis

Abstract: Persistence of intracellular infection depends on the exploitation of factors that negatively regulate the host immune response. In this study, we elucidated the role of macrophage PGE2, an immunoregulatory lipid, in successful survival of Leishmania donovani, causative agent of the fatal visceral leishmaniasis. PGE2 production was induced during infection and resulted in increased cAMP level in peritoneal macrophages through G protein–coupled E-series prostanoid (EP) receptors. Among four different EPs (EP1–4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 50 publications
3
70
1
Order By: Relevance
“…Recently, our group has shown the importance of eicosanoids in modulating immune responses in Leishmania infection12. In addition, PGE2 has been shown to contribute to parasite proliferation1116, whereas LTB4 increases macrophage activation and intracellular destruction171819. Therefore, the balance between these two mediators seems to contribute to the control of Leishmania infection and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group has shown the importance of eicosanoids in modulating immune responses in Leishmania infection12. In addition, PGE2 has been shown to contribute to parasite proliferation1116, whereas LTB4 increases macrophage activation and intracellular destruction171819. Therefore, the balance between these two mediators seems to contribute to the control of Leishmania infection and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established that L. donovani infection induces PGE2 release from infected macrophages (13,14), which involves upregulation of Cox2. Our lab has previously reported increased Cox2 expression during L. donovani infection (17).…”
Section: Resultsmentioning
confidence: 99%
“…Human monocytes have exhibited increased PGE2 production following Leishmania infection (13). The importance of PGE2 in the progression of VL is critical, as disease progression is arrested in PGE2-inhibited macrophages (14). This study aimed to elucidate the signaling phenomena responsible for L. donovani-induced PGE2 generation in an attempt to understand which components can be modulated to block its immunosuppressive effects.…”
mentioning
confidence: 99%
“…Studies have shown that the COX pathway and its downstream lipid mediators regulate chemokine expression in inflammation. Inhibition of COX-2 augmented CCL3 (MIP-1α) and CCL5 (RANTES) expression by Leishmania -infected peritoneal macrophages (24). PGE 2 attenuated LPS-induced mRNA and protein expression of CXCL-10 (IP-10) and CCL3 in mouse adipose tissue (25).…”
Section: Introductionmentioning
confidence: 99%